2018
DOI: 10.1007/s11356-018-1213-1
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of organics extracted from dewatered sludge by alkaline pretreatment in microbial electrolysis cell

Abstract: Waste activated sludge in China are mostly subjected to dewatering process before final disposal without stabilization. This study investigated the feasibility of organics degradation and H production from non-stabilized dewatered sludge (DS) by microbial electrolysis cells (MECs). Alkaline pretreatment was used to disintegrate sludge matrix and solubilize organic matters in DS. Then, the treatment performance of DS supernatant in a single-chamber MEC at various applied voltages was investigated. The COD (chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Previous studies have shown that a minimum external voltage of 0.4-0.6 V is required to produce a significant amount of hydrogen, but further increase in voltage beyond 0.8 V is incapable of improving current density [13]. Moreover, our previous study [12] has observed a notable difference in organics degradation at 0.5 V and 0.7 V when treating WAS. So, herein, the variations of 0.5 V and 0.7 V were chosen to investigate the impact of the applied voltage.…”
Section: Mec Operationmentioning
confidence: 76%
See 3 more Smart Citations
“…Previous studies have shown that a minimum external voltage of 0.4-0.6 V is required to produce a significant amount of hydrogen, but further increase in voltage beyond 0.8 V is incapable of improving current density [13]. Moreover, our previous study [12] has observed a notable difference in organics degradation at 0.5 V and 0.7 V when treating WAS. So, herein, the variations of 0.5 V and 0.7 V were chosen to investigate the impact of the applied voltage.…”
Section: Mec Operationmentioning
confidence: 76%
“…The F/T-treated DS was fed with nutrient solution [11] into long-term running single-chamber MECs. Each MEC was constructed according to the previous report [12] with effective volume of 400 mL.…”
Section: Mec Operationmentioning
confidence: 99%
See 2 more Smart Citations
“…In China, most WWTPs were not built with or run anaerobic digesters due to technical hurdles and capital and operational cost. Most often, the sewage sludge is only subjected to concentrating and dewatering treatment processes . Li et al .…”
Section: Applications Of the Microbial Electrolysis Cellmentioning
confidence: 99%